DINAMIKA SOSIAL MASYARAKAT PUCANGAN: TRANSFORMASI STAIN MENUJU UIN SURAKARTA TAHUN 1997-2021 - Rafif Ahmad Fahreza; Qisthi Faradina Ilma Mahanani; Latif Kusairi (UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This study aims to examine the social conditions of the community surrounding Pucangan, Kartasura, as well as the institutional transformation process of the State Islamic College (STAIN) Surakarta into an institute and eventually into UIN Raden Mas Said Surakarta. Kartasura, as an area with historical significance and a strategic geographical position, has experienced significant changes in social, economic, and cultural aspects. This research employs the historical method, consisting of heuristics, verification, interpretation, and historiography. In addition, a social approach was applied through the use of archival sources, interviews, and literature studies to analyze the changes that have occurred over time. The findings reveal that the transformation in Kartasura has generated positive impacts, including increased economic activities, infrastructure development, and broader educational and employment opportunities for the local community. However, these transformations have also brought several challenges, such as shifts in local cultural values, increasing population density, and changes in patterns of social interaction within the community. Keywords: Transformation, Society, Pucangan.